Strengthening Household Solid Waste Management in Sierra Leone: Lessons from South Korea and Indonesia - Jalloh, Mohamed Yayah; Dahalan, Wan Siti Adibah Wan; Khalid, Rasyikah Md; Wulandari, Wulandari (Universitas Negeri Semarang, 2024)
Household solid waste (HSW) generation and its illegal disposal pose significant challenges to Sierra Leone, leading to public health and environmental harm. While municipal by-laws are implemented to deal with HSW in Sierra Leone, existing literature shows significant inadequacies in these laws. This paper employs normative legal research to examine the relevant laws in Sierra Leone and their adequacy and discusses related laws in South Korea and Indonesia. The findings reveal significant areas for improvement in Sierra Leone's laws, regulations, and policies pertaining to HSW, such as the absence of specific provisions to address HSW and the non-binding nature of existing provisions. Observing the relevant laws and measures in South Korea and Indonesia could significantly improve Sierra Leone's waste laws, leading to better HSW minimization. The proposed measures include establishing clear and specific laws and regulations for HSW management, implementing stricter penalties for HSW violations, promoting public awareness and education on waste reduction and recycling, and providing incentives for waste reduction and recycling. By doing so, Sierra Leone can improve public health, protect the environment, and promote sustainable development.